A coordinated optimization of rewarded users and employees in relocating station-based shared electric vehicles - Yu, Lan; Liu, Jiaming; Suo, Zhuo (Zielona Góra: Uniwersytet Zielonogórski)
To solve the mismatch between the supply and demand of shared electric vehicles (SEVs) caused by the uneven distribution of SEVs in space and time, an SEV relocating optimization model is designed based on a reward mechanism. The aim of the model is to achieve a cost-minimized rebalancing of the SEV system. Users are guided to attend the relocating SEVs by a reward mechanism, and employees can continuously relocate multiple SEVs before returning to the supply site.
Keywords: shared electric vehicles; user reward mechanism; collaborative relocating; SCE-UA